Sel Kumulus Sebagai Feeder Layer pada Kultur Stem Cells Embrionic Mencit (CUMULUS CELLS AS FEEDER LAYER IN CULTURE OF MOUSE EMBRYONIC STEM CELLS) - Hine, Thomas Mata; Boediono, Arief; Supriatna, Iman; Sajuthi, Dondin (Jurnal Veteriner; Vol 13 No 2 (2012), 2013)
The purpose of this study was to verify the effectiveness of cumulus cells as a feeder layer in supportingthe growth of mouse embryonic stem cells. Embryos at blastocyst stage were exposed in pronase solution,and then incubated in rabbit anti-mouse antibody and guinea pig complement to lyse and separate thetrophoblast cells from the inner cell mass. Inner cell mass subsequently cultured in a petri dish containinga cumulus feeder layer, mouse embryonic fibroblasts, or without a feeder layer, in stem cells medium. Theresulting stem cells colony passaged in trypsin solution, pipetted repeatedly to produce subcolonies orsingle cells, and cultured as before in some new petri dishes. Characterization of stem cells was identifiedby using alkaline phosphatase staining. The results showed the effectiveness of cumulus cells as feederlayer for culture of mouse embryonic stem cells was comparable with mouse embryonic fibroblasts, andboth of them were better than without a feeder layer method. The number of primary colony, cell lines, andcolony growth rate increased 41.30, 8.70, and 54.20%, respectively, while doubling time was shorter 10:21hours compared to the growth without feeder layer method. These results prove that the cumulus feederlayer effectively supports the growth of mouse embryonic stem cells.
Keywords: feeder layer, cumulus, embryonic stem cells, mouse